2022
DOI: 10.1177/15347354221096868
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Propolis as an Adjunctive Therapy in Breast Cancers

Abstract: Propolis is a resinous beehive product that has a wide range of biological activities, namely antimicrobial, antioxidant, and anti-inflammatory properties. Propolis is collected by the bees from plant resin and exudates to protect hives and maintain hive homeostasis. The aim of the present systematic scoping review is to explore the potential and suitability of propolis as an adjunctive treatment in breast cancers, based on the latest available experimental evidence (2012-2021). After applying the exclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Therefore, the use of anti-inflammatory compounds has been linked to lower the risk of cancers, namely esophageal, stomach, liver, and pancreatic cancer [ 38 ]. Propolis, as a natural product, with its anti-inflammatory properties could potentially play a role in alleviating cancer progression and its associated symptoms [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of anti-inflammatory compounds has been linked to lower the risk of cancers, namely esophageal, stomach, liver, and pancreatic cancer [ 38 ]. Propolis, as a natural product, with its anti-inflammatory properties could potentially play a role in alleviating cancer progression and its associated symptoms [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Historical records show that ancient Egyptians, Greeks, Persians, Romans, Indians, Mayans, and Australian Aborigines independently developed the therapeutic use of propolis. The more recent scientific research demonstrates that the therapeutic properties of propolis are due to its content of plant secondary metabolites such as phenolics and terpenoids [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hermansyah et al., (2022) [19] describe four human clinical trials that demonstrated the use of propolis in alleviating side effects of chemotherapy and radiotherapy while increasing the quality of life of breast cancer patients, with minimal adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Several bioactive compounds present in propolis, e. g., artepillin C, inhibit the migration and invasion of cells of some types of cancer. [18] Hermansyah et al, (2022) [19] describe four human clinical trials that demonstrated the use of propolis in alleviating side effects of chemotherapy and radiotherapy while increasing the quality of life of breast cancer patients, with minimal adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is a resinous beehive product that is collected by bees from plant exudates and is used to protect and maintain hive homeostasis [ 1 , 2 ]. Propolis has been used by humans therapeutically to treat inflammation and infectious diseases [ 3 , 4 , 5 , 6 , 7 , 8 ]. Numerous studies have revealed a range of biological activities of propolis, including antibacterial, antifungal, antiviral, anticancer, anti-inflammatory, immunomodulatory, and antioxidant activities [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%